D-105 Reversible HIV-1 Latency Induced in Primary Human Monocyte-Derived Macrophages by Repeated M1 Polarization. (April 2018) - Graziano, Francesca; Aimola, Giulia; Forlani, Greta; Turrini, Filippo; Accolla, Roberto; Vicenzi, Elisa; Poli, Guido
Abstract : The contribution of tissue-associated macrophages to the viral reservoir in HIV-1 infected individuals receiving cART remains highly debated. In this regard, we have previously reported that functional M1 polarization of primary human MDM by short-term (18 h) stimulation with pro-inflammatory cytokines (IFN-γ plus TNF-α) leads to a significant containment of virus replication. Here, we demonstrate that restimulation of infected M1-MDM with the same pro-inflammatory cytokines 7 days after infection (M12 MDM) leads to a superior containment of virus replication to near undetectable levels, as determined by RT activity released in culture supernatants, in comparison to both control (CTR) MDM and to M1-MDM that were not restimulated by polarizing cytokines. M12 MDM showed an upregulation of APOBEC3A and 3G, with a significant reduction of HIV DNA and virtual lack of viral mRNA expression together with the expression of transcriptional inhibitors of proviral gene expression, namely CIITA and TRIM22, although expression and phosphorylation of transcriptional inducers of HIV-1 provirus, such as NF-kB and STAT-1, were not impaired. Latently infected M12-MDM harbored replication-competent virus that was promptly reactivated by allogeneic PHA blasts or their culture supernatant. Thus, our study provides a formal demonstration that a state of reversible latent HIV-1 infection can be established in primary human MDM upon their repeated M1 polarization by stimulation with pro-inflammatory cytokines before and after in vitro infection leading to a dominance of restrictive over permissive factors.